Corporate social responsibility and earning management: Evidence from listed Vietnamese companies - Ngoc Mai Tran; Manh Ha Tran; Thuy Duong Phan (Cogent Business & Management, 2022)
The purpose of this paper is to examine the association between corporate social responsibility (CSR) and earning management of listed Vietnamese companies. Both accrual earning management (AEM) and real earning management (REM) are calculated on yearly basis from 2016-2020. Information on CSR is extracted from the top 100 sustainable businesses announced by Vietnam Chamber of Commerce and Industry (VCCI). Using Feasible Generalized Least Squares (FGLS) method, this study finds negative relationship between CSR and earning management. High socially responsible firms are less likely to engage in earning manipulation, for both AEM and REM. In other words, these firms are less likely to obscure true economic performance by changing accounting methods or altering the real business transactions. The study is the first to examine the impact of CSR on both AEM and REM in the context of Vietnam. It also provides important implications for shareholders, stakeholders and related authorities using CSR as a sign of quality of reported financial information.
Keywords: M14; M4; 650; corporate social responsibility; CSR; earning management